Inclusive Governance (Incgov): Reformasi Pengawasan Dana Desa untuk Mengurangi Prevalensi Kemiskinan Ekstrem di Kabupaten Batang - Setiawan, Hendy (Bestuurskunde: Journal of Governmental Studies, 2025)
Extreme poverty remains a persistent challenge in Batang Regency, despite the increased allocation of The Village Fund from the central government since 2015. This challenge is further compounded by cases of corruption in the use of The Village Fund in several villages. Therefore, reforming the Village Fund oversight through an inclusive governance approach is essential to ensure accountability and promote the reduction of extreme poverty. This study employed a qualitative descriptive method with a literature review. Data were collected through searches of relevant secondary sources and analyzed using the Spradley technique, which involved domain analysis, taxonomy, componential analysis, and cultural theme analysis. The findings indicate that the limited human resource capacity of village officials remains a critical barrier to achieving meaningful participation. The disbursement of The Village Fund in Batang Regency was not accompanied by improved capacity of the program administrators, which created challenges to participation from both village human resources and the broader community, which largely remained passive. The Village Fund oversight reforms, which were often dominated by external mechanisms, had a significant impact on governance outcomes. However, reliance on external oversight alone still led to cases of corruption, underscoring the importance of strengthening internal mechanisms through a more inclusive community approach. Therefore, oversight reforms should be developed with a focus on inclusive governance, integrating both internal and external dimensions.